Development of Cloud Messaging-Based Mobile Learning Application to Improve Interaction in the Learning Process at STIKI (ebelajar case study) - Perdana, Derajat Aalim (IC-ITECHS, 2024)
In the digital era, the use of technology in the learning process is crucial to improve the effectiveness and efficiency of education. This study aims to develop a cloud messaging-based mobile learning application to improve interaction between students and lecturers at STIKI. This application is developed using the Dart programming language with the Flutter framework and utilizes cloud messaging technology to enable fast and effective communication in the form of announcements, discussions, and task notifications. The research method used is the research and development (R&D) method with the Agile software development model. The development stages include needs analysis, design, implementation, and application testing and evaluation. The results of the study show that this mobile learning application can increase the frequency and quality of interaction in the learning process. This increase is measured through user satisfaction surveys and analysis of application usage data. With this application, it is expected to provide a positive contribution in increasing student involvement in the teaching and learning process, as well as making it easier for lecturers to deliver materials and information related to lectures. This study also presents recommendations for further development so that the application can continue to be adjusted to user needs and technological developments.